Supply Chain Collaboration as an Innovative Approach of Warehouse Management: A Case Study - Kučera, Tomáš; Hyršlová, Jaroslava (Vysoká škola ekonomická v Praze, 2016)
Supply chain management, especially supply chain collaboration is a very much discussed topic in the field of modern logistics in recent years. Supply chain management is the term for the systems, resources, activities and procedures that are used to coordinate the materials, products, services, finance and information flows from materials suppliers through manufacturers, transporters, warehouses, wholesalers and retailers to consumers. Effective supply chain management is an essential strategy for company success in global and e-markets to get products to market faster and at minimal total costs. Supply chain collaboration is a total coordination and integration function which enables company easier and more effective using of available resources, to successfully reduce total costs, to provide and sustain the sub-contracting relationships. The objective of supply chain collaboration is to achieve sustainable competitive advantage. This paper deals with supply chain collaboration issue as an innovative approach of warehouse management in a case study. The paper shows supply chain collaboration between supplier of logistic services and manufacturer of automotive parts and discusses options which can make a synergy effect in application to practice.
Dodavatelsko-odběratelská spolupráce jako inovativní přístup skladového hospodářství: Případová studie
Keywords: supply chain management; collaborative initiatives; logistic services; logistic costs; řízení dodavatelsko-odběratelského řetězce; spolupráce v rámci dodavatelsko-odběratelského řetězce; logistické služby; logistické náklady